The Engagement between Knowledge Transfer and Requirements Engineering - Mirja Vaananen; Harri Haapasalo; Anyanitha Distanont; Jari Lehto (International School for Social and Business Studies, 2012)
Developing requirements in the early phase of product development is a processthat poses considerable challenges. The most significant challenge ishow to effectively transfer knowledge-related requirements. This paper highlightsthe challenges related to knowledge transfer practices, while developingrequirements through a review of literature and an analysis of high-techcompany interviews. The most significant challenges and their effects on practicesare also discussed. We found that the roots of any difficulty in requirementstransfer were embedded in the failure to transfer knowledge-relatedrequirements and facilitate communication between stakeholders. This difficultyaffects stakeholders' common understanding. Therefore, interpretationsof the requirements vary and do not match the stakeholders' intentions.Lastly, the final requirements and specifications sent are unclear and ambiguousso the requirements need to be changed and modified.